A multicriteria-optimization model for cultural heritage renovation projects and public-private partnerships in the hospitality industry - Tavana, Madjid; Azadmanesh, Abdolreza; Nasr, Arash Khalili; Mina, Hassan (Current Issues in Tourism)
Keywords: Tourism; Leisure and Hospitality Management; Geography; Planning and Development

A new algorithm for modeling online search behavior and studying ranking reliability variations - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Applied Intelligence)

A New Particle Swarm Optimization Algorithm for Optimizing Big Data Clustering - Hashemi, Seyed Emadedin; Tavana, Madjid; Bakhshi, Maryam (SN Computer Science)

A novel Interval Type-2 Fuzzy best-worst method and combined compromise solution for evaluating eco-friendly packaging alternatives - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Bonyani, Abbas (Expert Systems with Applications)
Keywords: Artificial Intelligence; Computer Science Applications; General Engineering

A parameter tuned hybrid algorithm for solving flow shop scheduling problems with parallel assembly stages - Jabbari, Mona; Tavana, Madjid; Fattahi, Parviz; Daneshamooz, Fatemeh (Sustainable Operations and Computers)

A private sustainable partner selection model for green public-private partnerships and regional economic development - Tavana, Madjid; Khalili Nasr, Arash; Mina, Hassan; Michnik, Jerzy (Socio-Economic Planning Sciences)
Keywords: Management Science and Operations Research; Statistics; Probability and Uncertainty; Strategy and Management; Economics and Econometrics; Geography; Planning and Development

A Renaissance of Context in Design Science Research - zur Heiden, Philipp; Beverungen, Daniel (Proceedings of the 55th Hawaii International Conference on System Sciences)

A Review of Digital Transformation on Supply Chain Process Management Using Text Mining - Tavana, Madjid; Shaabani, Akram; Raeesi Vanani, Iman; Kumar Gangadhari, Rajan (Processes)

A Rollercoaster of Emotions – A Semantic Analysis of Fundraising Campaigns over the Course of the COVID-19 Pandemic - Grieger, Nicole; Seutter, Janina; Kundisch, Dennis (Proceedings of the 28th Americas Conference on Information Systems (AMCIS))

A socio-economic and environmental vulnerability assessment model with causal relationships in electric power supply chains - Vafadarnikjoo, Amin; Tavana, Madjid; Chalvatzis, Konstantinos; Botelho, Tiago (Socio-Economic Planning Sciences)

A stochastic bi-objective simulation–optimization model for cascade disaster location-allocation-distribution problems - Khalili-Damghani, Kaveh; Tavana, Madjid; Ghasemi, Peiman (Annals of Operations Research)
Keywords: Management Science and Operations Research; General Decision Sciences

A technology development framework for scenario planning and futures studies using causal modeling - Tavana, Madjid; Ghasrikhouzani, Mohsen; Abtahi, Amir-Reza (Technology Analysis & Strategic Management)
Keywords: Management Science and Operations Research; Strategy and Management

AI-Based Assistance System for Manufacturing - Deppe, Sahar; Brandt, Lukas; Brünninghaus, Marc; Papenkordt, Jörg; Heindorf, Stefan; Tschirner-Vinke, Gudrun
Manufacturing companies are challenged to make the increasingly complex work processes equally manageable for all employees to prevent an impending loss of competence. In this contribution, an intelligent assistance system is proposed enabling employees to help themselves in the workplace and provide them with competence-related support. This results in increasing the short- and long-term efficiency of problem solving in companies.
Keywords: Assistance system; Knowledge graph; Information retrieval; Neural networks; AR

AI-Based Assistance System for Manufacturing - Deppe, Sahar; Brandt, Lukas; Brunninghaus, Marc; Papenkordt, Jörg; Heindorf, Stefan; Tschirner-Vinke, Gudrun (2022 IEEE 27th International Conference on Emerging Technologies and Factory Automation (ETFA))

Aktuelle Fragestellungen zu Produktion, Controlling und Logistik

Alte Fotografien, neue Erkenntnisse - Liszt-Rohlf, Verena; Wochnik, Markus; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

An Economic Analysis of Mergers and Aquisitions - The case of Facebook and WhatsApp - Yeboah, Amoabeng

An efficient model-based branch-and-price algorithm for unrelated-parallel machine batching and scheduling problems - Shahvari, Omid; Logendran, Rasaratnam; Tavana, Madjid (Journal of Scheduling)

An extended hybrid fuzzy multi-criteria decision model for sustainable and resilient supplier selection - Afrasiabi, Ahmadreza; Tavana, Madjid; Di Caprio, Debora (Environmental Science and Pollution Research)

An information retrieval benchmarking model of satisficing and impatient users’ behavior in online search environments - Di Caprio, Debora; Santos-Arteaga, Francisco J.; Tavana, Madjid (Expert Systems with Applications)